Circulating kidney injury molecule-1 is a novel diagnostic biomarker for renal dysfunction during long-term adefovir therapy in chronic hepatitis B. Issue 44 (November 2016) - Li, Ziyue; Shen, Chuan; Wang, Yadong; Wang, Wei; Zhao, Qian; Liu, Zhenzhong; Wang, Yang; Zhao, Caiyan
Abstract : Abstract: The aim of this study was to evaluate serum kidney injury molecule-1 (KIM-1) as a new diagnostic marker of renal dysfunction in chronic hepatitis B (CHB) patients receiving long-term adefovir dipivoxil (ADV) treatment. We retrospectively enrolled 85 patients treated with ADV and 85 patients treated with entecavir (ETV) monotherapy, for at least 6 months. The 2 groups were matched for baseline age (± 5 years), sex, and estimated glomerular filtration rate (eGFR). Serum creatinine, cystatin C, and KIM-1 concentrations were measured, and eGFR was calculated using the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) creatinine–cystatin C equation, at baseline and last follow-up. eGFR decreased by 10–20% from baseline in 11/85 (14.1%) patients, 20–30% in 5/85 (5.9%), and ≥ 30% in 2/85 (2.4%) patients treated with ADV. Serum KIM-1 was more significantly increased after ADV treatment 86.53 (10.20–355.40) pg/mL than ETV treatment 61.54 (10.53–200.56) pg/mL ( P < 0.01). Furthermore, serum KIM-1 was positively correlated with serum cystatin C ( r = 0.47; P < 0.001) and negatively correlated with eGFR ( r = -0.46; P < 0.001). The area under the receiver operating characteristic curve (AUC-ROC) of serum KIM-1 for identifying renal dysfunction in all enrolled patients was 0.94 (95% confidence interval [95% CI], 0.87 to 1.02; P < 0.001), while the AUC-ROC of serum creatinine was only 0.82 (95% CI, 0.60 to 1.03; P < 0.01). Serum KIM-1 is a promising new diagnostic biomarker of renal dysfunction during long-term ADV therapy for CHB patients. Abstract : Supplemental Digital Content is available in the text